SOCIAL SUPPORT IN POLAND – SELECTED ISSUES - Dębski, S.; Kowalski, D.; Nikolenko, O.; Kyryk, O.; Orel, I. (Rehabilitation and Recreation, 2022)
Social support as a multidimensional and multifaceted concept arouses interest in many fields and scientific disciplines. It is definitely one of the main elements of the emerging democracy, understood as people’s rule, i. e. the management of society on the territory of its country. This idea is derived from the content of the laws shaped at the turn of human history in the formula of the right to self-determination of nations. The state is currently not clearly defined. For the sake of these scientific considerations, in the process of reduction, we assume that the state is the inhabitants of the territory separated by the boundaries recognized by law. In the continuous process of democratization of the socio-political system of Poland, institutional forms shaping the so-called social support. The society obtains the possibility of permanent or temporary institutional support in extraordinary or unusual situations in the material sense. The mobilization of funds for these purposes, both centrally and locally, is to meet the needs of the population as soon as they appear. Formulas were introduced administratively that define to whom and in what circumstances and in what form the support is granted. The purpose of the support is to mobilize financial and material resources depending on the circumstances of the applicants. The commissioning procedures are covered in a timespan. Many institutions have been constructed in such a way as to trigger a decision- making and settlement imperative in them in a relationship shaping the assessment and remuneration of officials depending on the full use of funds for the indicated purposes. Not all possible targets are listed for obvious reasons – it is impossible to predict everything. Nevertheless, the time conditions for spending the funds were strictly defined, causing the action and decision pressure on which the amount of remuneration of officials and their regularity were dependent. This dominated the clerical activities to such an extent that it forced the construction of an official-needy relationship for the benefit of a stable arrangement in the interests of both parties. This leads now to the implementation of the scheme of constant granting support to certain people in need, forced by the indicated circumstances, and instructing them about the possibilities of using also options other than those established at the moment of their appearance, thus shaping the lack of will of those in need to change their situation and role from the needy to the role of the worker and paying taxes from which funds are created for supporting institutions, their employees and clients. The role of the client in the system of long-term use in the psychological sense excludes the possibility of change without the use of therapeutic forms. The lack of these forms, meaning that they can be used by all those in need, closes the clerk-client-therapist circle and determines the durability of the system. This creates numerous research challenges. The most difficult element and the most adhering to his convictions and blocking any changes of roles is the person of the official. In this study, selected issues occurring in Poland are subjected to research methods.